Projeto Pafundi: criança feliz aprende melhor! Afroletramento, transversalidade e pertencimento afro na escola: uma experiência pretagógica - Mendonça, Esther Costa (2020)
This investigation is an intervention research with an anti-racist perspective that has as its theme the strengthening of the sense of belonging of students from a peripheral school through strategies of African literacy. Set in a public school of elementary level I, located in the João Paulo II neighborhood, in the Grande Jangurussu, in Fortaleza, it has as protagonists two classes of the 5th year, totaling a total of 70 students. He started from the following questions: what are the benefits that pretagogy can bring in the strengthening of afro belonging when experiences of African literacy and transversalization of subjects are carried out? What are the elements of transversalization of the curriculum that can be achieved through experiences of African literacy? Which operative concepts of pretagogy and possible pedagogical practices can be used to generate an afroletragem of students within the scope of the school curriculum in action. Pretagogical intervention was carried out in the curricular components of Portuguese, Literature, Sciences, History, Geography, Arts and Human Formation. To this end, field and documentary research were carried out, with data being collected through observation of classes, workshops and field classes where the feedback collection was provided for each intervention. At the beginning of the research, a historical contextualization about the education of the black population was presented through a survey of milestones that contributed to the advances in black education and anti-racist education in Brazil, as well as discussion of studies on racism in the classroom. Then came the discussion on diversified literacies with an emphasis on the design and application of African literacy, which proposes the decentralization of educational practices, enabling new cultural and critical perceptions from an afre-referenced perspective. The theoretical-methodological framework adopted in the empirical approach was Pretagogy, which supported the investigation, both from a philosophical and operational point of view. Emphasis was placed on the markers of Africanities that make it possible to identify recurring elements of the presence of Africanities in Brazilian life and society, regardless of ethnic-racial belonging. In this way, students were able to realize the importance of Africanities in their lives. The work used some operational concepts such as the transfer of knowledge. As a theoretical basis, works by Petit (2015), Boal (1980), Cuti (2010), Freire (1993), Gomes (2017), Cavalleiro (2000), among others, were used. Legal documents from Brazil (2003, 2004, 2010) were also referenced, which discuss the mandatory teaching of ethnic-racial relations, status of social equality, national guidelines for the education of ethnic-racial relations. It is concluded that the classes experienced an afro-literacy process integrated with the school curriculum that favored anti-racist attitudes, stimulating the recognition and pride of the blackness of black children and / or black people in the family or references. In this way, the use of literature, music, historical, geographical, artistic exploration from black authors talking about the blackness and the presence of this blackness in the country's culture and other experiences provided during the research-intervention proved to be very pertinent to the strengthening of Afro belonging and combating racism in the classroom.